TREATMENT OF POST-COVID HERPETIC NEURALGIA OF THE TRIGEMAL NERVE (Web of Teachers: Inderscience Research, 2025)
The intensity and suddenness of pain syndrome, as well as the recurring nature of its attacks, lead to physical psychological exhaustion and provide grounds to consider trigeminal neuralgia as one of the most difficult diseases to endure.